The Effect of Vibration on Pain During Intravenous Injection of Propofol: A Randomized Controlled Trial. Issue 1 (July 2021) - Hwang, Lyahn K.; Nash, David W.; Yedlin, Adam; Greige, Nicolas; Larios-Valencia, Jessie; Choice, Curtis; Pothula, Aravind
Abstract : Purpose: Pain is a common side effect of intravenous injection of propofol. We conducted a randomized, prospective, single-blinded controlled trial to assess the efficacy of vibration analgesia on pain during propofol infusion in ambulatory surgery. Methods: After institutional review board approval, 100 patients undergoing elective ambulatory surgery with general anesthesia were randomized into 2 groups. A control group (n = 50) consisted of patients who received infusion of propofol without vibration analgesia. A treatment group (n = 50) consisted of patients who received infusion of propofol with vibration analgesia using the Buzzy device. Pain was assessed using a 4-point pain manifestation scale scored by 2 independent, blinded observers. Results: Participants in the treatment group with vibration analgesia were 0.47 times less likely (95% confidence interval, 0.24–0.94; P = 0.03) to experience any pain than the control group. The median summative pain score in the treatment group was significantly less than that of the control group [1 (interquartile range, 1–2) vs 2 (interquartile range, 2–4); P < 0.01] among participants who experienced any pain. Agreement between the 2 blinded observers regarding pain scores was excellent with κ w = 0.82 ( P < 0.001). Age, sex, body mass index, needle location or size, and medication doses did not differ significantly between the 2 groups. Conclusion: Vibration analgesia is an effective, low-risk modality that reduces the pain of intravenous propofol injection in general anesthesia.